Experimental infection by haemonchus contortus in lambs: Influence of disease on purine levels in serum - Gressler L.T. (2014)
SUMMARY The aim of this study was to evaluate the purine levels of lambs experimentally infected with Haemonchus contortus. A total of 12 healthy lambs were divided into two groups, composed of 6 animals each: Group A represented the healthy animals (uninfected), while in Group B the animals were infected with 15 000 larvae of H. contortus. Blood was drawn on days 15, 45 and 75 post-infection (PI) in order to perform the purine analysis (ATP, ADP, AMP, adenosine, inosine, hypoxanthine, xanthine and uric acid) by high pressure liquid chromatography (HPLC) in serum. On day 15 PI a significant (P<0·05) increase in the levels of ATP and inosine was observed in the infected animals, unlike the levels of ADP, adenosine, xanthine and uric acid which were reduced. On day 45 PI a significant (P<0·05) increase in the ATP and xanthine levels in infected animals was observed, contrasting with reduced levels of ADP and uric acid. Finally, on day 75 PI an increase occurred in the levels of ATP, adenosine and hypoxanthine in infected lambs, concomitant with a reduction in the levels of ADP and uric acid (P<0·05). These changes in purine levels may influence the inflammatory process and the pathological events. © 2014 Cambridge University Press .